Coping with Demographic Change in Job Markets: How Age Diversity Management Contributes to Organisational Performance. (February 2015) - Bieling, Gisela; Stock, Ruth Maria; Dorozalla, Florian
Demographic shifts are altering job markets in developed countries. A steady increase in the average age of employees and a decline in the number of young, qualified workers have intensified the war for talent, resulting in highly competitive and dynamic job markets. Using resource dependence theory, this study investigates how organisations respond to such challenges. An investigation of a sample of 153 German companies provides support for the hypotheses that HR managers implement age diversity management in both appraisal and compensation practices as a response to competitive job markets which, in turn, contributes to organisational performance.